The Level of Public Knowledge of Gastrointestinal Drug Self-medication for Gastritis Patients at Talita Pharmacy, Makassar City - Zulfiah, Zulfiah; Kadang, Yuniharce; Ferlita, Dika (Jurnal Farmasi Sandi Karsa, 2023)
Diseases of the gastrointestinal tract are quite dangerous diseases that cause many deaths number 6 in the world. Based on data from the WHO (World Health Organization), diseases of the gastrointestinal tract mostly occur in developing countries by looking at the prevalence rates of gastrointestinal diseases that occur due to disruption of the digestive system. human digestion. Poor eating habits can cause various digestive disorders such as heartburn, diarrhea, dizziness, difficult bowel movements, nausea, flatulence and fever. Gastritis is a digestive tract disorder caused by three main factors, such as (a) H. pylori (b) long-term use of Non-Steroid Anti-inflammatory Drugs (NSAIDs), and (c) Stress-Related Musocal Damage (SRMD). In addition, gastritis can also be caused by other factors, such as irregular eating patterns, consumption of coffee, tea, cola, alcohol and spicy foods, and stressful conditions. Gastritis sufferers will experience complaints including stomach pain, nausea, vomiting, weakness, flatulence, and feeling tight, pain in the pit of the stomach, no appetite, pale face, increased body temperature, cold sweat, dizziness or belching and bleeding can also occur digestive tract. The purpose of this study was to determine the level of public knowledge of self-medication of digestive tract drugs for gastritis patients at the Talita Pharmacy in Makassar City. The research method uses quantitative analysis with descriptive surveys, namely research that includes surveys with data collection techniques in the form of questionnaires. The results of the study showed that: Based on the results of the data obtained from this study, it can be concluded that the level of knowledge of the community regarding self-medication of digestive tract drugs for gastritis patients at the Talita Pharmacy in Makassar City with age criteria of 15-50 years, can communicate well, is willing to be a respondent and is classified as high with a percentage of 83%, the data shows that the level of public knowledge of self-medication of digestive tract drugs for gastritis patients at the Talita Pharmacy in Makassar is included in the tofu category.